Heteromeric Kainate Receptors Formed by the Coassembly of GluR5, GluR6, and GluR7 - Cui, Changhai (J Neurosci, 1999)
In the CNS kainate subtype glutamate receptors (GluRs) are likely to be heteromeric assemblies containing multiple gene products. However, although recombinant kainate receptors from the GluR5–GluR7 gene family have been studied extensively in their homomeric forms, there have been no tests to determine whether these subunits can coassemble with each other. We used the GluR5 selective agonists (RS)-2-amino-3-(3-hydroxy-5-tertbutylisoxazol-4-yl)propanoic acid (ATPA) and (S)-5-iodowillardiine (I-will) to test for the coassembly of GluR5 with GluR6 and GluR7 by measuring changes in rectification that occur for heteromeric receptors containing both edited and unedited Q/R site subunits. Birectifying ATPA and I-will responses resulting from polyamine block for homomeric GluR5(Q) became outwardly rectifying when GluR6(R) was coexpressed with GluR5(Q), although GluR6 was not activated by ATPA or I-will, indicating the formation of heteromeric receptors. Similar approaches showed the coassembly of GluR7 with GluR6 and GluR5. Heteromeric kainate receptors containing both GluR5 and GluR6 subunits exhibited novel functional properties, including reduced desensitization and faster recovery from desensitization than those recorded for homomeric GluR5. Coexpression of GluR6 with GluR5 also enhanced the magnitude of responses to GluR5 selective agonists. In contrast, the coassembly of GluR7 with GluR6 markedly decreased the amplitude of agonist responses. Our results indicate that, similar to AMPA receptors, the kainate receptor subunits GluR5–GluR7 exhibit promiscuous coassembly. The formation of heteromeric kainate receptors may help to explain why the functional properties of native kainate receptors differ from those that have been reported for recombinant kainate receptors.